Cross-Border Jurisdictional and Legal Issues of Biometric Data Protection in Indonesia (International Forum of Researchers and Lecturers, 2025)
The rapid advancement of digital technology, particularly in personal data processing, has significantly increased the collection and utilization of biometric data, which includes unique biological characteristics such as fingerprints, facial features, voice patterns, and iris scans. Biometric data is highly sensitive, immutable, and directly linked to an individual's identity, making its misuse or unauthorized disclosure a serious and permanent threat to privacy rights. This research examines the adequacy of legal protection provided by Law Number 27 of 2022 on Personal Data Protection (PDP Law) in Indonesia, with a specific focus on jurisdictional challenges in cross-border contexts—especially when foreign entities, such as Worldcoin, process such data. The primary objective of this study is to evaluate the role of the PDP Law in safeguarding biometric data and to identify potential legal and practical barriers in cross-border enforcement. The study adopts a normative-empirical legal approach, integrating juridical analysis, legislative review, and conceptual examination, while also taking into account technological developments such as artificial intelligence and blockchain-based identity systems. The findings indicate that while the PDP Law represents a substantial milestone in Indonesia’s data protection framework, significant structural limitations remain. These include the absence of detailed implementing regulations, insufficient institutional oversight, and the lack of effective international cooperation mechanisms. Such gaps hinder the enforcement of biometric data protection, particularly in cross-border scenarios. To address these challenges, the study recommends several measures: strengthening technical regulations, establishing a robust supervisory authority, and developing comprehensive cross-border legal frameworks aligned with international standards. Furthermore, collaboration among the government, private sector, and civil society is essential to create a biometric data protection ecosystem that is both adaptive and resilient to rapid global technological changes. By doing so, Indonesia can enhance the protection of its citizens' biometric data while fostering trust in the digital economy.